2019
DOI: 10.1186/s12944-019-1119-z
|View full text |Cite
|
Sign up to set email alerts
|

Terminalia Arjuna bark extract impedes foam cell formation and promotes apoptosis in ox-LDL-stimulated macrophages by enhancing UPR-CHOP pathway

Abstract: BackgroundIncreased macrophage and foam cell apoptosis during early atherogenesis retards plaque progression by impeding foam cell formation, suppressing inflammation and limiting lesion cellularity. Our previous in vitro study in THP1 macrophages demonstrated that Terminalia Arjuna (TA) attenuates dual-specificity phosphatase1 (DUSP1), a key negative regulator of JNK/P38MAPK signaling cascade, the branch also implicated in the UPR (unfolded protein response)-CHOP-mediated apoptotic pathway; however this pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…Therefore, we used 100 μg/mL ox-LDL to induce the formation of foam cells in subsequent experiments. The same concentration of ox-LDL (100 μg/mL) has been reported in other studies [23]. Next, we assessed the effect of QUE on RAW264.7 cell viability.…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, we used 100 μg/mL ox-LDL to induce the formation of foam cells in subsequent experiments. The same concentration of ox-LDL (100 μg/mL) has been reported in other studies [23]. Next, we assessed the effect of QUE on RAW264.7 cell viability.…”
Section: Resultsmentioning
confidence: 98%
“…Additionally, such cytoplasmic fluorescence signal was significantly stronger for ox-LDL-stimulated RAW264.7 cells (Fig. 3 b: *** P < 0.001 vs. unstimulated cells), which might benefit from the upregulated expression of CD36 on macrophages after ox-LDL treatment [ 20 ]. The western blot result further showed that the expression of CD36 was increased in ox-LDL-treated RAW264.7 cells ( P < 0.05 ox-LDL stimulation group vs. control group) (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that CD36, which is expressed on the surface of macrophage, is a key regulatory point for the formation and development of AS. It can mediate the conversion of macrophage into foam cell after phagocytosis of ox-LDL [ 19 , 20 ]. AntiCD36 can specifically bind to CD36 and inhibit macrophage phagocytosis of ox-LDL [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 82 ] However, when stress is overloaded or prolonged, the UPR becomes maladaptive and triggers apoptotic cell death through activating cell death pathways such as caspase-4, c-Jun NH2 terminal kinase, and C/EBP homologous protein. [ 83 85 ] ER stress may cause fibrosis through AEC apoptosis, EMT, myofibroblast differentiation, and M2 macrophage polarization. [ 14 – 16 ]…”
Section: Various Imbalances Centered On An Apoptosis Imbalance In Aecmentioning
confidence: 99%